Combination Therapy of Guajava Leaf Powder (Psidium Guajava L) and Turmeric Powder (Curcuma Domestica Val) to Cure Diarrhea in Sheep - Ajar Budiarji; Sunarsih, Sunarsih; Andanawari, Suci; Zulfikhar, Rosa; Akbarrizki, Muzizat; Sukoco, Hendro; Cahyani, Annisa Putri (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the therapeutic effect of guava leaf powder and turmeric powder on the healing of diarrhea in sheep. This study used a completely randomized design (CRD) with four treatments, each consisting of three repetitions. P0 treatment as a control in three sheep and nine sheep for P1, P2, and P3 treatments with different doses (400 mg/kg BW, 500 mg/kg BW, 600 mg/kg BW). Parameters assessed were frequency of defecation, consistency, and color of sheep feces. The combined treatment of guava leaf powder and turmeric powder on sheep diarrhea was analyzed using ANOVA statistical analysis and Duncan's further test after scoring changes in healing. The result of the ANOVA analysis was a significant difference of 0.007 (P<0.01) on Day 3 compared to Day 1 and Day 2. Duncan's further test was that P0 was not significantly different from P1 but significantly different from P2 and P3. P1 was not significantly different from P0 and P2 but significantly different from P3. P2 was significantly different from P0 but not significantly different from P1 and P3, while P3 with P0 and P1 showed significantly different but not significantly different from P2.